Association analysis of charcoal rot disease component traits in sorghum minicore germplasm with EST-SSR markers - Harsha Kumar, B. N.; Bhat, Sumangala; Borphukan, B.; Fakrudin, B. (The Indian Journal of Genetics and Plant Breeding, 2017)
Sorghum is an important crop of semi arid regions where it suffers from several biotic stresses. Among biotic stresses, charcoal rot/stalk rot is a major constraint for rabi (post rainy) sorghum production. Identification of stable resistant sources and incorporation of the genes or quantitative trait loci (QTL1) governing resistance are the prerequisite to make progress in breeding for charcoal rot resistance. A set of 242 sorghum minicore collection were phenotyped in sick plot of charcoal rot disease. A total of 31 polymorphic EST-SSR markers were developed and mapped through association analysis. The population structure analysis indicated the partitioning of the genetic population structure into four clusters. In the current study six new markers were identified for charcoal rot disease resistance (Xiabt 210, Xiabt 527, Xiabt 301, Xiabt 37, Xiabt 77, Xiabt 81) and was validated previously identified flanking markers for charcoal rot disease QTLs (locus Xiabt 275) at RARS Vijayapura location. Six marker trait associations were stable at two locations and these significant associations are useful and suitable for marker assisted selection in charcoal rot disease resistance breeding programs.